Association between Internet Addiction and Sleep disturbance Among Nursing Students - Ahmed, Mahmoud Mohammed; Younis, Nasir Muwfaq; Hussein, Ahmed Ali (International Journal of Psychosocial Rehabilitation, 2020)
Background:Internet addiction was described as an inability to regulate the use of Internet, arising in marked distress or loss of function in daily activities. Objectives: The purpose of this article is to describe the related between (IA) and sleep disorder among nursing students in Mosul City / Iraq. Materials and Method: A survey of (120) nursing students in Mosul / Iraq was conducted. "Young‟s Internet Addiction Scale” (IAS) was used to describe association between (IA) and sleep troubles. Results: The results from the analysis show association between the sleep disturbance and (IA) is high significant, also found higher sleep disturbance rates especially difficulty waking from sleep. Conclusion: The findings of the study are concluded that the participants from nursing students have sleep disturbance, also more a higher addiction of internet and have problem of sleep is associated with excessive Internet use.